Asymptomatic Pellet Migration to the Heart: Report of a Case and Update on Proper Management - George Galyfos; Konstantinos Palogos; Nikolaos Kavouras (Case Reports in Surgery)
We report a case of a 42-year-old male patient who was transferred to our emergency department suffering from a gunshot wound in his left lateral thigh. The patient was haemodynamically stable, and the physical examination of the abdomen and thorax was unremarkable. There was no obvious exit point and there were no other injuries. The radiologic control of the left thigh showed an intact femur and multiple pellets within the adjacent soft tissues. Routine X-ray evaluation of the thorax revealed a small-sized round object of metal density—possibly a migrated pellet—in the proximity of the right heart atrium. Computed tomography imaging confirmed this finding and showed no other cardiac or mediastinal injury. Ultrasonography of the heart was unremarkable as well. The patient was managed conservatively for the discovered pellet, and remained asymptomatic throughout the entire hospital stay, and 6 months after the discharge. Pellet migration or embolism should be suspected in any gunshot victim without a corresponding exit wound or when the signs and symptoms do not correlate with the suspected course of the missile. Conservative management remains the first choice in asymptomatic patients, although close monitoring at first and regular observation after discharge are indicated.